A novel service discovery algorithm via service repository centre in internet of things. (2017) - Jia, Bing; Zhou, Tao; Zhang, Chuxuan
In recent years, the internet of things (IoT) has attracted more and more attention, and IoT services have increased rapidly. The service discovery which has important implications for the service integration of IoT services has become more difficult in large-scale registration. In traditional matching method, in order to get a better match results, all the matching parameters for services had to be calculated together, thus it would waste a lot of computing resources and computing time. This paper propose a centralise four-layer model for service discovery via multi-stage semantic service matching to improve the performance of service discovery, namely interactive interface layer, parsing annotation layer, service matching layer and data semantic layer, so as to meet the requirement of service discovery in large-scale IoT services. We also propose a hybrid service matching degree measurement by synthetically calculating the concept logic and semantic similarity for each layer singly. Experimental analysis confirms the effectiveness of the proposed mechanism in improving the precision and recall.